APA PERKEMBANGAN TERBARU SEJARAH KEWIRAUSAHAAN DI ERA INDUSTRI 4.0? - Rusnandari Retno Cahyani (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2020)
The current industrial revolution 4.0 affects the historical development of entrepreneurship. Important activities to bring about change in the economy and society not only in a country but also people in the world. Big changes are not only in concept and definition, but more towards the implementation of entrepreneurship which is increasingly modern and digitalization in various lines. Entrepreneurship in its current development is in the era of the industrial revolution 4.0 which will prepare for the next era changes.